2003
DOI: 10.1177/003693300304800403
|View full text |Cite
|
Sign up to set email alerts
|

No Excess Risk of Adverse Birth Outcomes in Populations Living near Special Waste Landfill Sites in Scotland

Abstract: A recent study showed small excess risks of low birth weight, very low birth weight and certain congenital anomalies in populations living near landfill sites in Great Britain. The objective of the current study was to investigate the risk of adverse birth outcomes associated with residence near special waste landfill sites in Scotland. We studied risks of adverse birth outcomes in populations living within 2 km of 61 Scottish special waste landfill sites operational at some time between 1982 and 1997 compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 15 publications
(1 reference statement)
1
31
0
Order By: Relevance
“…In a study of air and soil pollution levels in 19 Swedish municipalities, Landgren (1996) found no increase in low birth weight or preterm deliveries in the municipalities with the highest concentrations of pollutants compared with all others. Morris et al (2003) found no statistically significant excess risk of low birth weight in populations living near special waste landfill sites in Scotland. In contrast, after controlling for potential confounders, Sram et al (1996) report an increased frequency of low birth weight deliveries in a heavily industrial region of the Czech Republic compared with the control region.…”
Section: Residential Exposure To Industrial Waste and Reproductive Hementioning
confidence: 71%
“…In a study of air and soil pollution levels in 19 Swedish municipalities, Landgren (1996) found no increase in low birth weight or preterm deliveries in the municipalities with the highest concentrations of pollutants compared with all others. Morris et al (2003) found no statistically significant excess risk of low birth weight in populations living near special waste landfill sites in Scotland. In contrast, after controlling for potential confounders, Sram et al (1996) report an increased frequency of low birth weight deliveries in a heavily industrial region of the Czech Republic compared with the control region.…”
Section: Residential Exposure To Industrial Waste and Reproductive Hementioning
confidence: 71%
“…As for the paternal side, some jobs carry increased risks such as vehicle operators, police officers or fire fighters [Schnitzer et al, 1995] and men exposed to dust from grinding metals [Brouwers et al, 2010]. For people living close to hazardous waste-disposal sites, the risk was first described as minor [Elliott et al, 2001], but this has also been refuted [Morris et al, 2003]. …”
Section: Environmental Factors and Hypospadiasmentioning
confidence: 99%
“…However, no significant positive association was observe for stillbirthBaibergenova et al 2003 [28]Ecologic study of New York (excluding New York City)(1994–2000) USVLBW, LBW PCB-contaminated site Exposure defined as maternal residence at birth in a zip code that contained or was adjacent to a PCB-contaminated siteSex of the baby, race of the mother, mother’s age, father’s age, mother’s educational level, parents annual per capita income, Medicaid/self-paid births, Maternal weightSingle motherhoodMaternal smokingMultiplelogistic modelsStratification by sex of the babySlight association noted for risk of low birth weight in male births and maternal residence in zip code with one or more waste sites contaminated with PCBs. But, no relation between PCB zip codes and very low-birth-weight infants for either sexMorris et al 2003 [47]Ecologic study in Scotland (1982–1997)Great BritainAll congenital anomalies Specific defect. NTD, cardiovascular, and abdominal wall defects; hypospadias and epispadias; surgical correction of hypospadias and epispadias; surgical correction of gastroschisis and exomphalos; Birth outcome.…”
Section: Methodsmentioning
confidence: 99%